2022
DOI: 10.1136/bmjopen-2021-053559
|View full text |Cite
|
Sign up to set email alerts
|

KETOgenic diet therapy in patients with HEPatocellular adenoma: study protocol of a matched interventional cohort study

Abstract: IntroductionHepatocellular adenoma (HCA) is an uncommon, solid and benign liver lesion, mainly occurring in women using oral contraceptives. Patients are advised to stop using oral contraceptives (OC) and, as overweight is frequently observed, dietary restrictions. Metabolic changes are assumed to play a role and it has been suggested that diet may help to reduce tumour size. A low-calorie ketogenic diet (LCKD) has been shown to induce weight loss and multiple metabolic changes, including the reduction of port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…A prospective interventional study is currently being conducted to assess the effect of a low-calorie ketogenic diet on the evolution of HCA. [27] Moreover, weight gain should be discouraged in patients with HCA and a normal BMI at diagnosis. Our data suggested also that progestin-only-based contraception seems safe in women with residual HCAs even though the current study was not specifically designed to answer this question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective interventional study is currently being conducted to assess the effect of a low-calorie ketogenic diet on the evolution of HCA. [27] Moreover, weight gain should be discouraged in patients with HCA and a normal BMI at diagnosis. Our data suggested also that progestin-only-based contraception seems safe in women with residual HCAs even though the current study was not specifically designed to answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to estrogen‐based contraception discontinuation, these data suggested that weight loss should be actively encouraged in patients with HCAs who are overweight or obese. A prospective interventional study is currently being conducted to assess the effect of a low‐calorie ketogenic diet on the evolution of HCA 27. Moreover, weight gain should be discouraged in patients with HCA and a normal BMI at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…We selected 200 email addresses of healthcare professionals from departments associated with the active clinical trials 29–31. The survey was sent twice, on 26 April 2023 and 10 May 2023, and people were given a response window of 6 weeks from 26 April 2023.…”
Section: Methodsmentioning
confidence: 99%
“…Contents and protocol on this investigational product have been published earlier 6. At the start of the presentation, colleagues were informed about the content of the presentation; an update on the active clinical trials investigating STF 29–31. After this brief introduction, they received information about the current randomised study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation